Lower limb venous haemodynamic impairment on dependency: quantification and implications for the “economy class” position - Delis, Konstantinos T.; Knaggs, Alison L.; Sonecha, Tans N.; Zervas, Vasileios; Jenkins, Michael P.; Wolfe, John H. N. (Thrombosis and Haemostasis, 2004)
The role of stasis in venous disease is undisputed, yet surprisingly, its haemodynamic quantitation remains largely undefined. We investigated the phenomenon of venous stasis in the lower limb upon sitting and standing and project its implications to economy class aircraft passengers. 26 normal limbs, 13 subjects, age 29-54, selected after duplex, plethysmography and ABPI, had peak[Vpeak], mean[Vmean] and minimum[Vmin] velocities, volumeflow[Qvenous], pulsatility index [PIvenous] and diameter obtained on horizontal, sitting (as in economy aircraft seats) and standing with duplex, at popliteal, femoral[FV] and common femoral[CFV]veins [differences in median %]. Vpeak, Vmean and Qvenous decreased from horizontal to sitting in the CFV [57%, 71%, 31%, respectively], FV [51%, 70%, 34%] and popliteal [31%, 58%, 42%] (all, p<.001). Vpeak, Vmean and Qvenous decreased further from sitting to standing in the CFV [26%, 44%, 25%, respectively], FV [21%, 42%, 27%] and popliteal [14%, 42%, 20%] (all, p <.001). Diameter, Vmin and PIvenous increased from horizontal to sitting in the CFV [50%, 63%, 38%, respectively], FV [39%, 23%, 66%] and popliteal [21%, 14%, 84%] (all, p <.001)]. Diameter, Vmin and PIvenous increased further from sitting to standing in CFV [10%, 22%, 19%, respectively; p ≤.004], FV [12%, 68%, 2%[ns]; p <.001)] and popliteal [14%, 50%, 24%; p ≤.017]. In all postures: Vpeak, Vmean, Qvenous and diameter at CFV exceeded FV (p <.025) and popliteal (p <.001) ones; also those at FV exceeded the popliteal ones (p ≤.003), except for the diameter on horizontal. Vmin in popliteal was higher than in CFV (p ≤.003) or FV (p <.025), on horizontal and standing. PIvenous in CFV was lower than in FV or popliteal (p <.025) on sitting. Right to left differences nonsignificant. [Wilcoxon+Bonferroni test: significance at p <.025] A shift from horizontal to sitting generates a most significant attenuation in Qvenous, Vpeak and Vmean linked to a reciprocal increase in Vmin, PIvenous and vein diameter, with further exacerbation on standing. Vpeak, Vmean and Qvenous decline with distance from groin enhancing venous stasis in the periphery. By restricting activation of the natural venous pumps, sitting cramped during long flights may protract the status of haemodynamic stagnation sustained on dependency which paired with marked venous dilatation generates a milieu that may promote thrombogenesis.
Keywords: Venous stasis; haemodynamics; dependency; flow quantification; coagulation; economy class